(untitled) (Journal of Engineering, 2007)
In this research dissimilar welds were made of low carbon steel (A516) and austenitic stainless steel (316L) by shielded metal arc welding (SMAW) and with different electrodes (E7018) , (E6013) , (E309L) and (E308L). The sheet thickness (6 mm), welding current (120 A), voltage (78V), polarity (DCRP) and electrode diameter (3.25 mm) were remained constant. Many tests were carried out, mechanical tests included tensile test, bending and microhardness also made , and metallurgical inspections included microstructure, delta- ferrite phase and x- ray diffraction analysis. It was found from tensile and bending tests results that the electrode (E309L) was the most convenient for dissimilar welds of base metal (C.St. A516) and (St. St. 316L). Hardness tests showed that the highest hardness value appears in (HAZ) and there are two peaks of maximum hardness, each peak value in each (HAZ) for both dissimilar metals, the peak values are not equal and the higher value appears in the zone, where the electrode differ from the base metal, i. e. when the electrode is used (E6013) the higher value appeared in the (HAZ) which is near the stainless steel (316L), and when the electrode (E309L) is used, the higher value appeared in (HAZ) near the low carbon steel (A516) .The tests demonstrated that the delta (δ) ferrite phase was about 3-10% near stainless steel and for all used electrodes.